Sosialisasi Upaya Pencegahan Stunting Melalui Pengenalan Makanan Sehat Untuk Ibu Dan Balita Di Desa Kebondalem Kabupaten Temanggung - Musfika, Bella; Fibrianti, Nurul; Misrinah, Misrinah (Universitas Negeri Semarang, 2023)
The issue of stunting is an important issue that has gone global. One of the factors is due to socioeconomic conditions with high levels of poverty and lack of knowledge. An important period that should continue to concern mothers is in the first 1000 days of the child's life. One way to reduce stunting rates is by socializing stunting prevention. This socialization activity was carried out by the UNNES GIAT KKN Team in collaboration with posyandu cadres and local puskesmas officers. This activity is also one of the implementations of community service which is summarized in the Tri Dharma of Higher Education. This activity uses observation, interview, and socialization methods by introducing simple healthy foods. Healthy food is a perfect 4 healthy 5 food, where there are carbohydrates, proteins, fats, and vitamins. The results of this socialization show that mothers understand better about stunting and its characteristics and understand prevention efforts.